The Meaningful Tourism Paradigm – A Tool for Sustainable Tourism Development in Times of Crises and Challenges - Arlt, Wolfgang Georg (Language Assistance, 2025)
Confronted by converging crises – climate change, AI-driven disruption, and shifting traveler demands – traditional sustainable tourism models struggle with